2007
DOI: 10.1007/s00122-007-0588-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of rice transgene flow in compass sectors by using male sterile line as a pollen detector

Abstract: Rice is the most important staple food in the world. The rapid development of transgenic rice and its future commercialization have raised concerns regarding transgene flow and its potential environmental risk. It is known that rice is a self-pollinated crop; the outcrossing rate between common cultivars is generally less than 1%. In order to improve the detection sensitivity of rice transgene flow, a male sterile (ms) line BoA with a high outcrossing rate was used as a pollen detector in this study. A concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…Especially cultivated japonica rice has a very low out-crossing rate and their pollen have a very short life span (several minutes) so most of out-crossing happen within 1 m. As shown in tables, gene flow event was very rare to find beyond 90 cm range. The distance of pollen dispersal increases with wind speed and direction but it does not mean that cross-pollination will occur against self-pollinated crops at a distance of over 1 m. Within hybrid rice production through male-sterile rice (MS), in general, maximum distance of gene flow is known to be about 40-60 m Yuan et al 2007). In the production of hybrid rice using MS line, more than 100 m isolation distance has been recommended in China (Yuan and Fu 1995).…”
Section: Gm To Non-gm Gene Flow Eventmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially cultivated japonica rice has a very low out-crossing rate and their pollen have a very short life span (several minutes) so most of out-crossing happen within 1 m. As shown in tables, gene flow event was very rare to find beyond 90 cm range. The distance of pollen dispersal increases with wind speed and direction but it does not mean that cross-pollination will occur against self-pollinated crops at a distance of over 1 m. Within hybrid rice production through male-sterile rice (MS), in general, maximum distance of gene flow is known to be about 40-60 m Yuan et al 2007). In the production of hybrid rice using MS line, more than 100 m isolation distance has been recommended in China (Yuan and Fu 1995).…”
Section: Gm To Non-gm Gene Flow Eventmentioning
confidence: 99%
“…Even though the out-crossing rate between cultivated rice and weedy rice is very low, both have high sexual compatibility (Song et al 2002;Song et al 2003;Song et al 2004;Messeguer et al 2004). Several studies that used male-sterile lines reported that rice pollen can be dispersed to more than 100 m Jia et al 2007;Yuan et al 2007). With this information, gene flow from cultivated rice to wild or weedy rice was proven to be continuously happening in the field naturally.…”
Section: Introductionmentioning
confidence: 99%
“…These data suggest that pollen dispersal is more prevalent downwind, and thus wind direction influencing pollen distribution is a concern in preventing pollen contamination of GM crops. In one study of gene flow in compass sectors, approximately 10-fold cumulative gene flow was found in the 4 sectors downstream of the prevailing wind (90-96%), but only 4 −10% of this flow occurred in the 4 sectors upstream of the prevailing wind (Yuan et al 2007). The evidence of rice pollen-mediated gene flow revealed in this study was in accordance with maize pollen-mediated gene flow on the multi-year field experiments at several locations (Devos et al, 2005).…”
Section: The Effectiveness Of a Green Fence With Chinese Hibiscus In mentioning
confidence: 99%
“…The velocity and direction of wind are important vectors for pollen dispersal (Devos et al, 2005). The gene flow in populations downstream of prevailing wind was 6.47−26.4%, and that in populations upstream was only 0.39−3.03% (Yuan et al, 2007). Moreover, gene flow of 0.01% from transgenic rice to O. rufipogon was found at a distance of 250-m because of the high wind speed in Sanya, China (Wang et al, 2006).…”
mentioning
confidence: 99%
“…Previous studies found that GM rice may hybridize with traditional cultivars (Messeguer et al 2001(Messeguer et al , 2004Rong et al 2005Rong et al , 2007Jia et al 2007;Yuan et al 2007;Yao et al 2008), weedy rice (Zhang et al 2003(Zhang et al , 2006Chen et al 2004;Messeguer et al 2004;Sanchez Olguin et al 2009), and wild rice (Chen et al 2004;Yao et al 2008). A few GM rice lines have been developed in Korea, including those tolerant to herbicides (Lee et al 2007) and abiotic stresses (Jang et al 2003).…”
Section: Introductionmentioning
confidence: 98%